KORELASI TINGKAT STRES DENGAN KUALITAS TIDUR LANSIA: CORRELATION BETWEEN STRESS LEVELS AND SLEEP QUALITY ON ELDERLY - DEWI, NI PUTU RAHAYU INDRA; Lestari, Ni Kadek Yuni; Dewi, Ni Luh Putu Thrisna (Stikes Wira Medika Bali, 2020)
The aging process is a natural process which happens to human being, where at this stage physical condition, psychology and social change or decrease will happen. The change may cause the elderly undergo stress. Stress is a condition or situation which is caused by environmental change and considered to be challenging, threating or destructing someone’s dynamic balance. Stress which is not properly handled may influence the elderly’s sleep quality becomes poor. The research is aimed to recognize the correlation between the stress level and elderly’s quality sleep. The design of this research is descriptive correlation which the number of sample is 59 elderly which are taken by purposive sampling technique. The data collection was implemented by giving DASS and PSQI Questionnaires. The result of the research shows that most of elderly with medium level of stress are 24 people (40,7%) and elferly undergo poor sleep quality are 19 people (42,2%). The result of spearman test gains P value = 0,000 (p<a = 0,05) which indicates the existence of significant correlation between stress level and Elderly’s sleep quality at Panti Sosial Tresna Werdha Jara Mara Pati Singaraja. Coefficient Value is 0, 604 which indicates strong correlation between two variables with the points of positive correlation that the higher level of stress the poorer sleep quality will be. The Nurses/Attendant of Panti Sosial Tresna Werdha Jara Mara Pati Singaraja are suggested to hold or conduct special program which will enable to control the stress management for the elderly for example brain exercise or reminiscence therapy.